Effects of constant intravenous infusion of detomidine alone or combined with butorphanol or methadone for standing sedation in horses: A randomized clinical trial - Júnior, G. S. (2025)
This study aimed to evaluate the sedation degree, cardiopulmonary effects, and detomidine-sparing during dental occlusal adjustment in standing horses using a bolus and constant rate infusion (CRI) of detomidine alone or in combination with butorphanol or methadone. In this randomized, blinded clinical trial, 24 healthy adult horses were assigned to the detomidine (DT), detomidine-butorphanol (DB), or detomidine-methadone (DM) group. DT received an intravenous bolus of detomidine (20 μg/kg), followed by CRI at 20 μg/kg/h. DB received detomidine (10 μg/kg) and butorphanol (0.02 mg/kg) boluses with CRI at 10 μg/kg/h and 0.03 mg/kg/h, respectively. DM received detomidine (10 μg/kg) and methadone (0.2 mg/kg) boluses with CRI at 10 μg/kg/h and 0.05 mg/kg/h, respectively. For sedation rescue, an additional intravenous dose of detomidine (5 μg/kg) was administered without altering the CRI. Descriptive scales were used to assess sedation during and up to 12 h post-procedure. We recorded the respiratory rate (fr), heart rate (HR), systolic blood pressure (SBP), temperature, gastrointestinal motility, sedation depth, and detomidine rescue requirements. All treatments were found to reduce gastrointestinal motility and HR, whereas DM decreased fr. SBP exhibited transient elevations, and 22 sedation rescues were performed (2 in DM, 8 in DT, and 12 in DB). Considering the rescues, the total detomidine consumption resulted in significantly lower doses in DM (10.6 ± 2.32 μg/kg/h [mean ± standard deviation]) and DB (13.6 ± 4.58 μg/kg/h; both P < 0.0001) than in DT (22.4 ± 4.1 μg/kg/h). Opioid addition demonstrated a detomidine-sparing effect, significantly reducing detomidine requirement.